Avaliação da angiotensina II, angiotensina 1-7, receptor Mas e da enzima conversora de angiotensina 2 do sistema renina-angiotensina, em fetos com diagnóstico ultrassonográfico de crescimento intrauterino restrito - Juliana Silva Barra (2009)
Introduction/objective: Studies demonstrate that the angiotensina renina system has significant function in the regulation of the sanguineous flow placentary uterus e, therefore, in the fetal development. Methods: Ultrassonografics and dopplerfluxometrics criteria of restriction of the intrauterine growth that had been divided in the groups small for thegestacional age (PIG) and adjusted for the gestacional age (AIG) and later subdivided in minors or equal the 35 weeks or greaters had been studied embryos with that 35 weeks. At the moment of the cesariana ml of blood of the umbilical lace and maternal blood had been harvested 10, from which dosage for radioimunensaio of the peptideos was made. Theimunoexpressão of the same ones was seen in the placenta and umbilical lace. Results/conclusion: We verify that the expression of Angiotensina II tends to be bigger in the placenta of the embryos with CIUR below of 35 weeks, even so without difference statistics. We verify that the expression of angiotensina 1-7 tends to be bigger in theplacenta of embryos AIG, but did not have difference statistics for the small number of cases. The converting enzyme of angiotensina, ECA2, that converts angiotensina II and angiotensina 1-7, tends to have greater expression in the placenta of adequate embryos AIG. In the umbilical lace the expression of angiotensina II and angiotensina 1-7 tends to be increased in the embryos with CIUR, but it did not have difference statistics. The plasmatics levels of angiotensina II and angiotensina 1-7 had also not demonstrated difference. The maternal level of angiotensina II of the embryos with CIUR in relation to embryos AIG did not show estatítica difference. But the level of angiotensina 1-7 in the plasma maternal statistical meets in the group of embryos with CIUR in relation to the normal embryos below of 35 weeks, indicating possible participation of this peptideo in the regulation of the placentary sanguineous flow higher.